Comprehensive Molecular Characterization of Chinese Patients with Glioma by Extensive Next-Generation Sequencing Panel Analysis - Zeng, Chun (Cancer Manag Res, 2021)
BACKGROUND: Tremendous efforts have been made to explore biomarkers for classifying and grading glioma. However, the majority of the current understanding is based on public databases that might not accurately reflect the Asian population. Here, we investigated the genetic landscape of Chinese glioma patients using a validated multigene next-generation sequencing (NGS) panel to provide a strong rationale for the future classification and prognosis of glioma in this population. METHODS: We analyzed 83 samples, consisting of 71 initial treatments and 12 recurrent surgical tumors, from 81 Chinese patients with gliomas by performing multigene NGS with an Acornmed panel targeting 808 cancer-related hotspot genes, including genes related to glioma (hotspots, selected exons or complete coding sequences) and full-length SNPs located on chromosomes 1 and 19. RESULTS: A total of 76 (91.57%) glioma samples had at least one somatic mutation. The most commonly mutated genes were TP53, TERT, IDH1, PTEN, ATRX, and EGFR. Approximately one-third of cases exhibited more than one copy number variation. Of note, this study identified the amplification of genes, such as EGFR and PDGFRA, which were significantly associated with glioblastoma but had not been previously used for clinical classification (P<0.05). Significant differences in genomic profiles between different pathological subtypes and WHO grade were observed. Compared to the MSKCC database primarily comprised of Caucasians, H3F3A mutations and MET amplifications exhibited higher mutation rates, whereas TERT mutations and EGFR and CDKN2A/B copy number variations presented a lower mutation rate in Chinese patients with glioma (P<0.05). CONCLUSION: Our multigene NGS in the simultaneous evaluation of multiple relevant markers revealed several novel genetic alterations in Chinese patients with glioma. NGS-based molecular analysis is a reliable and effective method for diagnosing brain tumors, assisting clinicians in evaluating additional potential therapeutic options, such as targeted therapy, for glioma patients in different racial/ethnic groups.